Share repurchase and dividend payout behaviour: The South African experience - N. Wesson; B. W. Bruwer; W. D. Hamman (South African Journal of Business Management, 2015)
Share repurchases, rather than dividend payments, are increasingly becoming the globally favoured payout method. This has prompted a renewed interest in the field, and raises questions about the actual motivation for share repurchases and whether companies are now repurchasing shares in preference to investing in future growth. This study set out to ascertain whether South African company payout behaviour mirrors global company behaviour. Comprehensive data on share repurchases are, however, not compiled by South African financial data sources or by the Johannesburg Stock Exchange Ltd. In preparation for this study, the authors thus compiled the first comprehensive share repurchase database for companies in selected JSE-listed sectors for the first 11 years (i.e. 1999 to 2009) since share repurchases were first allowed in this country.Share repurchases were found to be a popular payout method, especially in the more recent periods covered in the study. Payout value was dominated by a few companies paying dividends every year and regularly repurchasing shares. Aspects unique to the South African regulatory environment, however, resulted in the South African share repurchase experience not fully mirroring current global practice. The main constraint in the South African share repurchase environment is that comprehensive, actual-time-based share repurchase data are not available. Recommendations are made on how to align the South African regulatory environment with global best practice. Regulatory changes, as well as continued research in the field, will equip stakeholders to make informed decisions.
Keywords: 650